(untitled) (El-Wahat Journal for Research and Studies, 2022)
ملخص تعد التربية المدنية نشاطا تربويا تستمد أسسها، و محتواها من الدراسات السياسية، والاجتماعية ، والقيمية، والاقتصادية، وهي من المواد التعليمية الاستراتيجية المدرجة في المناهج الدراسية، لما تحويه من مضامين وجهت سلوك الفرد عبر مراحل متعددة لأنها ليست من إفرازات العصر الحالي ، ولكن مقوماتها وجذورها، ودعائمها كانت متوفرة منذ زمن بعيد تمتد تاريخيا إلى ظهور الكائن البشري على وجه الأرض، علما أن التربية المدنية التي بدأت خلال مرحلة ما قبل التاريخ ليست هي نفسها التي كانت موجودة في العصور الوسطى ، وكذلك تختلف عن تلك التي عرفتها العصور الحديثة ، و الفترة المعاصرة. وعليه يتناول هذا البحث موضوع تطور التربية المدنية من خلال تتبع مسارها التاريخي بدءا من العصور ما قبل التاريخ إلى الفترة المعاصرة. كلمات دالة: التربية المدنية، مرحلة ما قبل التاريخ، العصر القديم، العصر الوسيط، العصر الحديث، الفترة المعاصرة Abstract Civic education is an educational activity whose foundations and content derive from political, social, value and economic studies, which are strategic educational materials included in the curriculum, because of the contents that directed the behavior of the individual through multiple stages because they are not from the secretions of the present era, but its components and roots, and its foundations, and its foundations, have been available for a long time historically extending to the emergence of the human being on earth, knowing that civic education that began during the prehistoric period is not the same as it existed in the Middle Ages, It is also different from those of modern times and the contemporary period. This research deals with the development of civic education by tracking its historical course from prehistoric times to the contemporary period. Key words: the civil education – Prehistoric - Ancient Times- Middle Ages- Modern Times- Contemporary Period